Aproximaciones a la justicia de paz en el Ecuador: Apuntes para su estudio e investigación. - Espinosa Ruiz, Camilo Isaac (2014)
In a culture of conflict and confrontation, violence and death are constant threats that conspire against the right to peace and life. In this difficult scenario, the ordinary justice seemed to be the only way to ensure public order and peace. However, past experience has shown that it is necessary to recover the essential values of society, reinstituting a culture of peace to ensure harmony and the right to a good life. In this utopia, justice of peace, recovering ancestral practices little valued, emerge in the context of the Judiciary Function as a valid alternative that aims to be efficient and effective to achieve natural human conflicts avoid being prosecuted and can be solved by the way of conciliation. Great are the efforts that Ecuador should do to not only institutionalize it, if not to consolidate it as a closer service to the citizenship, without involving the impersonation of ordinary justice. All must contribute to this noble purpose to make Ecuador a friendly country.